2020
DOI: 10.1186/s12888-020-02739-1
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of a virtual reality based, approach-avoidance training program for alcohol use disorder: a study protocol

Abstract: Background: The approach-avoidance training program (AATP) has shown preliminary promise as an add-on to standard treatment for alcohol dependence. However, knowledge is lacking as to whether the effectiveness of AATP can be enhanced further when performed in a typical drinking situation. The main aim of this study is to investigate whether approach-avoidance training implemented in a virtual reality bar environment is superior to the classical joystick PC-version of the AATP. Methods: The study will be implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 79 publications
0
9
0
1
Order By: Relevance
“…To evaluate the (cost-)effectiveness, relevant RCTs (level VR3), including adequate follow-up periods, need to be conducted. During our literature review, we identified five study protocols that report on planned RCTs and insights into potential new treatment mechanisms [77][78][79][80][81]. The studies focus on approach-avoidance training, mindfulness-based relapse prevention, memory-retrieval extinction and the use of pharmacotherapy (Isradipine) to enhance the effect of VRET on the extinction of craving.…”
Section: Future Outlookmentioning
confidence: 99%
“…To evaluate the (cost-)effectiveness, relevant RCTs (level VR3), including adequate follow-up periods, need to be conducted. During our literature review, we identified five study protocols that report on planned RCTs and insights into potential new treatment mechanisms [77][78][79][80][81]. The studies focus on approach-avoidance training, mindfulness-based relapse prevention, memory-retrieval extinction and the use of pharmacotherapy (Isradipine) to enhance the effect of VRET on the extinction of craving.…”
Section: Future Outlookmentioning
confidence: 99%
“…If this study demonstrates that AACTP is effective in patients with AUD, other means of assessing ABs and delivering cognitive training programs could be implemented by utilizing technologies such as virtual reality (VR) and augmented reality [AR; (89)]. These technologies have already been developed for targeting approach biases through the approach avoidance training program (90). Paradigms using VR and AR might overcome some of the shortcomings of the AACTP by increasing its ecological validity.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, Mellentin et al published a study protocol of a randomized controlled trial to examine the effectiveness of a stimuli-relevant approach-avoidance training programme (AATP) delivered in a VR environment compared to AATP without VR as well as in comparison to treatment as usual (TAU) in a large sample (estimated n = 204) of alcohol use disorder (AUD) patients [43]. The author hypothesized that AATP is more effective than TAU and VR AATP more effective than standard AATP.…”
Section: Vr-based Therapeutic Approachesmentioning
confidence: 99%